(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article presents the state-of-the-art research on the hydrogen fueled internal combustion engine. First, the fundamentals of the hydrogen engine are described by studying the engine-specific properties of hydrogen, and then the existing literature is reviewed.